FENOMENA ENDORSEMENT SEBAGAI TREN MEDIA PEMASARAN DIGITAL DI INDONESIA - Erlita Khrisinta Dewi; Citra Ayu Nur Kholifah (Nusantara Hasana Journal, 2022)
This study discusses the endorsement phenomenon as a digital marketing media trend. The theory used to discuss research problems is the Transcendental Phenomenological Theory of Edmund Husserl and marketing communication theory as the basis of the research. This research is a qualitative research with a descriptive design. The data used in this study are secondary data obtained from literature in the form of books, scientific papers, journals, articles, and other information related to the research title. The results of the study show that endorsements have been widely used by business people to market their products digitally. Endorsement is one of the effective marketing strategies chosen by business people in this digital era. Endorsement goes directly to prospective buyers and is also an easy, fast and cheap medium for achieving targets. Endorsements can drive a rapid rise in brand awareness of a product. Endorsement activities are increasingly in demand by the public in this digital marketing. Information technology is developing rapidly thus encouraging increased use of endorsements as a digital marketing media trend in Indonesia.